Pengaruh Perbandingan Modified Cassava Flour (Mocaf) dan Puree Wortel (Daucus carota L.) Terhadap Karakteristik Cake - Fardiaza, Gayatri Ayu; Timur Ina, Putu; Pratiwi, I Desak Putu Kartika (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
The study aims to determine the effect of comparison mocaf with carrot puree to the characteristics of cake and to find out the best comparison mocaf with carrot puree to produced cake with the best characteristics. The experimental design used in this research was a Completely Randomized Design (CRD) with a comparison of mocaf and carrot puree consisting of 6 treatments namely: 100%:0%; 90%:10%; 80%:20%; 70%:30%; 60%:40%; 50%:50%. The treatment was repeated 3 times so that they were obtained 15 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect then followed by Duncan’s Multiple Range Test (DMRT). The comparison of mocaf and carrot puree had a significant effect on water content, ash content, crude fiber, levels of betacarotene, antioxidant activity, hedonic test (color, texture), scoring test (color, flavor, taste, and overall acceptance). Ratio of 50% mocaf and 50% carrot puree had the best characteristics with water content 33.24%, ash content 1.24%, crude fiber 9.55%, levels of betacarotene 6.53 mg/100g, antioxidant activity 2.88 mg/ml, color were yellow and liked, pore uniformity were very equal and liked, texture were very soft and liked, aroma, taste and overall acceptance were liked.